EFEKTIVITAS PELAKSANAAN PIDANA PENJARA TERHADAPANAK NAKAL DI LEMBAGA PEMASYARAKATAN KELAS I SEMARANG - Krismiyarsi S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2008)
Any sentences ordered by the judge has significant implications for one's life. If a criminal sentence is ordered, the convict must be sent to prison for rehabilitation. The same condition applies for juvenile cases, in which the committed youth be put in a juvenile prison. Since Semarang has not established a juvenile prison, The delinquent youth were placed in the adult prison, although in separate units. This research investigates the effectiveness of criminal sentences applied to delinquency cases in class I Prison of Semarang. Jurisdiction sociological approach with qualitative analysis was used, utility both primary and secondary data. Result show that application of criminal sentences to delinquency cases were not effective sence the average length of imprisoned was three month. The delinquent youth were already detained for about two month, and only one month left for rehabilation. Rence, it was found different to rehabilitation. The youth such to equip them with vocational skills.